PENGARUH LATIHAN HARNESS PULL TERHADAP KECEPATAN LARI TIM FUTSAL PUTRA SMK MIGAS TEKNOLOGI RIAU - Marpaung, Dion; Zainur, Zainur; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
opponents or when they are about to snatch the ball from their opponents. Thistype of research is an experimental research design with One-Group Preetest PosttestDesign. The data in this study were the entire population of 10 people. With the 30 mrunning acceleration test instrument, descriptive analysis and the Liliefors test resultedin a pree-test Speed with an average of 4.49 then Harnes Pull exercise was carried outfor 16 meetings on the Men's Futsal Futsal Team of SMK Migas Teknologi Riau,totaling 10 people and the average post-test result was 4.36. Based on the pree-test andpost-test data analysis, there was an increase of 1.28. And based on inferentialstatistical analysis using the t-test, the t-count was 5.818 and the t-table was 1.833.Means tcount > ttable so it can be concluded that speed has an effect on the HarnessPull exercise needed to support the frequency when doing exercises to increase speed.Based on the results of the analysis, it can be concluded as follows: there is asignificant effect between Harness Pull (X) training on Speed (Y) in the Futsal Team ofSmk Migas Teknologi Riau.Key Words: Harness Pull Exercise, Running Speed